莱佩莱捷行星齿轮动力学仿真分析 - 李旭; 贾楠; 王文强; 李锐 (Jixie chuandong)
The Lepelletier planet gear mechanism is analyzed.By applying ADAMS software,the model of Lepelletier planet gear is constructed.The dynamics simulation is carried out,the meshing force curve is obtained and it can be used for analysis of stiffness and strength.